Fostering the acceptance of congestion charges: Experimental evidence for Europe - Manuel Frondel; Viola Helmers; Stephan Sommer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
Although there is ample empirical evidence that congestion charges can effectively reduce traffic congestion and its detrimental effects, this instrument has only been implemented in a handful European cities. On the basis of a randomized information experiment that was embedded in a survey across seven European countries, this paper empirically investigates whether information on their (i) effectiveness and (ii) a-posteriori acceptance may increase the public support for congestion charges. Relative to the control group, the results indicate that, on average, this information can raise acceptance by 9.3% and 7.1%, respectively. Moreover, while there is substantial heterogeneity in the acceptance across countries, attributing a concrete price level to the charge uniformly raises acceptance at low charge levels, but lowers it at high levels. Based on these results, we conclude that information campaigns on congestion charges and their benefits for commuters and city-dwellers are essential for fostering public support for this rarely employed transport policy instrument. – – Trotz zahlreicher Studien die belegen, dass eine Städtemaut die urbane Verkehrsüberlastung und ihre negativen Auswirkungen wirksam verringern kann, wurde dieses Instrument bisher nur in einer Handvoll europäischer Städte eingeführt. Auf Grundlage eines randomisierten Informationsexperiments, das in eine Umfrage in sieben europäischen Ländern eingebettet war, wird in dieser Studie empirisch untersucht, ob Informationen (i) über die Wirksamkeit und (ii) über a-posteriori Akzeptanz von bereits eingeführten Städtemauten die Unterstützung für eine solche Maßnahme beeinflussen können. Die Ergebnisse zeigen, dass die gegebenen Informationen die Akzeptanz unter den Befragten im Durchschnitt um 9,3 % bzw. 7,1 % erhöhen. Darüber hinaus ist die Akzeptanz in den einzelnen Ländern zwar unterschiedlich, aber die Zuweisung eines konkreten Preisniveaus für die Gebühr erhöht die Akzeptanz in allen Ländern bei niedrigen Gebühren und senkt sie bei hohen Gebühren. Auf der Grundlage dieser Ergebnisse kommen wir zu dem Schluss, dass Informationskampagnen über Staugebühren und ihre Vorteile für Pendler und Stadtbewohner wesentlich sind, um die öffentliche Unterstützung für dieses selten eingesetzte aber effektive verkehrspolitische Instrument zu fördern.
Keywords: R48; C25; 330; Acceptability; congestion charge; public support; road pricing